Luminescent labeling of leaves for remote monitoring of plants - Boyko, V.; Chornii, V.; Borysiuk, V.; Nedilko, S.; Suchocki, A. (Energy and Automation, 2025)
Luminescent markers are attracting increasing attention as a means of monitoring plant health due to the development of modern technologies for collecting, processing, and storing data necessary for precision agriculture. The combination of optical characteristics (reflection and emission of light) of markers (phosphors) and plant leaves allows remote monitoring, which contributes to the automation of the plant growing process. At the same time, the choice of the phosphor and the method of its application to the plant remains a relevant area of scientific research. In this work the results of the study of optical characteristics such as: diffuse reflection, photoluminescence (PL), and PL excitation spectra of leaves "before" and "after" the application of suspensions of two types: phosphor + water and phosphor + water + PVA, where the phosphor was SrAl2O4:Eu,Dy powder, have been analyzed. It was found that the application of suspensions of both types increases the diffuse reflection of light by leaves in the entire visible region., Three PL bands were observed in the photoluminescence spectra of untreated leaves: one of low intensity with a maximum at 535 nm, and two intense bands with maxima at 685 and 740 nm. The latter two bands of red luminescence correspond to the emission of the molecules of chlorophyll a, while the band at 535 nm may be ascribed to the emission of carotenoids in the leaves. The application of the SrAl2O4:Eu,Dy+H2O suspension practically does not lead to a change in the spectrum of intrinsic "red" PL of the leaves in the region of 625–825 nm. At the same time, for leaves coated with the SrAl2O4:Eu,Dy+H2O+PVA suspension, there is an increase in the luminescence intensity in the region of 450–650 nm, compared to the intensity of the band at 685 nm. The relative intensity of the PL band at 740 nm, however, decreases. It has been demonstrated that the PL spectra of the samples are sensitive to changes in the PL excitation wavelengths, ghat allows for selective excitation of the photoluminescence of the phosphor label and chlorophyll a contained in the leaf. The obtained results indicate the possibility of using the optical properties of leaves treated with suspensions to collect information about the condition of the plant, with the aim of applying the Internet of Things (IoT) concept in crop production. Key words: chlorophyll, light absorption, luminescent marker, photoluminescence